Intergenerational learning in Hong Kong: a narrative inquiry - Ho, Cherri (2008)
The main objective of this study was to examine the intergenerational learning behaviour within the family between Generation X parents and their Generation Y teenage children. This study was designed to investigate the nature of intergenerational knowledge exchange, to identify the characteristics of learning behaviour and culture in such 'learning families', and to find out the subject areas that parents could learn from their teenage children.